‘Prata Anã’ banana under application of paclobutrazol on soil and 2,4-D in the inflorescence in three production cycles: multivariate approach - Maia, Leonardo Carvalho Brant; Maia, Victor Martins; Azevedo, Alcinei Mistico; Ferreira, Evander Alves; Donato, Sérgio Luiz Rodrigues; Pereira, Marlon Cristian Toledo (Frontiers in Agronomy, 2025)
Paclobutrazol (PBZ) inhibits gibberellin biosynthesis and reduces plant size, whereas 2,4-D (2,4 dichlorophenoxyacetic acid) causes cell elongation and enhances fruit growth and productivity. In this study, we used a multivariate approach to evaluate the production and post-harvest characteristics of the ‘Prata-Anã’ banana in three production cycles after the application of paclobutrazol in the soil and 2,4-D during flowering. A randomized block design (4×4 factorial arrangement) was used, referring to the paclobutrazol (0, 0.1, 0.3, 0.5 g L-1) and 2,4-D concentrations (0, 10, 20, and 30 mg L-1), with three replicates. Five vegetative characteristics and one physiological characteristic were evaluated during plant flowering. Nine production variables were evaluated during harvest. The values of five production variables and two vegetative growth variables increased and the number of days between the clústeres decreased as the cycles progressed. 2,4-D did not affect the fruit production-associated characteristics. Further, 0.5 g a.i. (active ingredient), PBZ yielded lower and higher values for the production variables in the first and second production cycles, respectively. In the third cycle, 0.1 g a. i. paclobutrazol exerted the most prominent effect on the production variables, indicating that the plant response to growth regulators changes according to the production cycle.